Method for preparing lithium carbonate by utilizing amblygonite

By optimizing the process flow and selecting appropriate reagents and conditions, the method of preparing lithium carbonate by using phospholithium aluminite has solved the problems of low lithium yield and difficulty in removing impurities, and achieved efficient lithium recycling and sustainable development and utilization.

CN119461429APending Publication Date: 2025-02-18河南新天力循环科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995590.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Among the existing methods of preparing lithium carbonate using phosphorus lithium aluminite, the yield of lithium is low and it is difficult to effectively remove impurity ions, which affects product quality.

Method used

The first calcination treatment is performed by mixing the phosphorus lithium aluminite powder with inorganic acid, then mixing it with water to perform a first leaching treatment, then removing the phosphorus with iron salt, then mixing it with aluminum salt and sodium salt to perform a reaction, and finally performing the The second calcination and the second leaching treatment are carried out successively, and lithium precipitation treatments are obtained to obtain lithium carbonate.

Benefits of technology

Effectively remove impurities in phosphate lithium aluminite, improve the yield of lithium, and achieve efficient recovery of lithium. It also has the advantages of low energy consumption and environmentally friendly, supporting the sustainable development and utilization of lithium resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461429A_ABST
    Figure CN119461429A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing lithium carbonate by utilizing amblygonite, and relates to the field of metallurgy. The method for preparing lithium carbonate by utilizing the amblygonite comprises the following steps: carrying out first roasting treatment on amblygonite powder and inorganic acid to obtain clinker; mixing the clinker with water, carrying out first leaching treatment, and carrying out first solid-liquid separation to obtain first leachate and first leaching residues; the first leachate and ferric salt are subjected to a phosphorus removal reaction, and phosphorus removal liquid and phosphorus removal slag are obtained through second solid-liquid separation; reacting the dephosphorization liquid with aluminum salt and sodium salt, and carrying out third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent; carrying out second roasting treatment on the lithium adsorbent, carrying out second leaching treatment on a product after second roasting and water, and carrying out fourth solid-liquid separation to obtain lithium-rich liquid and lithium desorption slag; and the lithium-rich liquid is sequentially subjected to impurity removal treatment and lithium precipitation treatment, and lithium carbonate is obtained. According to the method, impurity ions in the amblygonite can be effectively removed, loss of lithium in the impurity removal process is avoided, and the purpose of efficiently recycling lithium is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metallurgy, and in particular to a method for preparing lithium carbonate using pyroxenite. Background Art

[0002] As a mineral resource rich in lithium, the development and utilization of pyroxenite is of great significance to meet the growing demand for lithium products. However, in the existing method of preparing lithium carbonate using pyroxenite, there is generally a problem of low lithium yield.

[0003] In the process of treating lithium aluminum phosphate with existing methods, it is often difficult to effectively remove impurity ions in lithium aluminum phosphate, which not only increases the difficulty of subsequent purification, but also may have an adverse effect on the quality of lithium carbonate products, and there is also the problem of low lithium yield. Summary of the invention

[0004] The purpose of this application is to provide a method for preparing lithium carbonate using pyroxenite to solve the above problems.

[0005] To achieve the above objectives, this application adopts the following technical solutions:

[0006] A method for preparing lithium carbonate using pyroxenite, comprising:

[0007] The phosphate lithium aluminum stone powder is mixed with an inorganic acid and subjected to a first roasting treatment to obtain a clinker;

[0008] The clinker is mixed with water, and subjected to a first leaching treatment, and a first leaching liquid and a first leaching residue are obtained through a first solid-liquid separation;

[0009] The first leaching solution is mixed with iron salt to perform a dephosphorization reaction, and a second solid-liquid separation is performed to obtain a dephosphorization liquid and a dephosphorization slag;

[0010] The dephosphorization liquid is mixed with aluminum salt and sodium salt to react, and then subjected to a third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent;

[0011] The lithium adsorbent is subjected to a second roasting treatment, the product after the second roasting is mixed with water, subjected to a second leaching treatment, and subjected to a fourth solid-liquid separation to obtain a lithium-rich solution and lithium-desorption slag;

[0012] The lithium-rich solution is sequentially subjected to impurity removal treatment and lithium precipitation treatment to obtain lithium carbonate.

[0013] According to an embodiment of the present application, the 200-mesh screening rate of the phosphate hematite powder is greater than 95%.

[0014] According to an embodiment of the present application, the inorganic acid includes one of sulfuric acid, hydrochloric acid, and nitric acid;

[0015] And / or, the mass ratio of the pyroxenite powder to the inorganic acid is 1:(0.3-0.8);

[0016] And / or, the temperature of the first calcination treatment is 500° C. to 700° C.;

[0017] And / or, the first calcination treatment time is 1 hour to 3 hours.

[0018] According to an embodiment of the present application, when the first leaching treatment is performed, the solid-liquid ratio of the clinker to water is 1:(5-10) g / ml;

[0019] and / or, the temperature of the first leaching treatment is 70° C. to 100° C.;

[0020] And / or, the first leaching treatment time is 0.5h to 2h.

[0021] According to an embodiment of the present application, the iron salt includes any one of ferric sulfate, ferric chloride, and ferric nitrate, and the anion of the iron salt is the same as the anion of the inorganic acid;

[0022] and / or, the ratio of the amount of iron in the iron salt to the amount of phosphorus in the first leachate is 1.0 to 1.05;

[0023] And / or, when performing the phosphorus removal reaction, the method further comprises adding sodium carbonate to the reaction system to adjust the pH of the system to between 1.5 and 1.8.

[0024] According to an embodiment of the present application, the temperature of the phosphorus removal reaction is 90°C to 95°C;

[0025] And / or, the phosphorus removal reaction time is 1 h to 2 h.

[0026] According to an embodiment of the present application, when the dephosphorization liquid reacts with the aluminum salt and the sodium salt, the method further comprises: adding ammonia water to the reaction system to adjust the pH of the system to between 8.0 and 10;

[0027] And / or, the aluminum salt includes any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion of the aluminum salt is the same as the anion of the inorganic acid;

[0028] And / or, the sodium salt includes any one of sodium sulfate, sodium chloride, and sodium nitrate, and the anion of the sodium salt is the same as the anion of the inorganic acid;

[0029] And / or, the amount of the aluminum salt and the sodium salt added is controlled so that after the aluminum salt and the sodium salt are added, the ratio of the amount of aluminum in the reaction system to the amount of lithium in the dephosphorization solution is 2 to 4, and the ratio of the amount of sodium in the sodium salt to the amount of aluminum in the reaction system is 3 to 5;

[0030] And / or, the temperature at which the dephosphorization liquid reacts with the aluminum salt and the sodium salt is 80° C. to 100° C.;

[0031] And / or, the phosphorus removal liquid reacts with the aluminum salt and the sodium salt for 2 hours to 4 hours.

[0032] According to an embodiment of the present application, the temperature of the second calcination treatment is 350° C. to 600° C.;

[0033] And / or, the second calcination treatment time is 0.5h to 2h;

[0034] and / or, during the second leaching treatment, the solid-to-liquid ratio of the second calcined product to water is 1:(3-5) g / ml;

[0035] and / or, the temperature of the second leaching treatment is 80° C. to 100° C.;

[0036] And / or, the second leaching treatment time is 0.5h to 2h.

[0037] According to an embodiment of the present application, the lithium-rich liquid is sequentially subjected to impurity removal treatment and lithium precipitation treatment, including: mixing the lithium-rich liquid with an alkaline solution, and obtaining a de-impurified liquid and calcium-magnesium slag through a fifth solid-liquid separation; and mixing the de-impurified liquid with sodium carbonate to obtain lithium carbonate.

[0038] According to an embodiment of the present application, the pH of the alkaline solution is 11 to 13;

[0039] And / or, the alkaline solution comprises sodium hydroxide.

[0040] Compared with the prior art, the beneficial effects of this application include:

[0041] The present application can effectively remove impurity ions in phosphate lithium aluminum stone by optimizing the process flow and selecting appropriate reagents and conditions, and also avoid the loss of lithium in the impurity removal process, so as to achieve the purpose of efficient lithium recovery. Moreover, the method of the present application also has the advantages of low energy consumption and environmental friendliness, providing strong support for the sustainable development and utilization of lithium resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0043] Figure 1 This is a flow chart of the method for preparing lithium carbonate using lithium aluminum phosphate in Example 1. DETAILED DESCRIPTION

[0044] As used herein:

[0045] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0046] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0047] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0048] In these examples, parts and percentages are by mass unless otherwise indicated.

[0049] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0050] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0051] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0052] A method for preparing lithium carbonate using pyroxenite, comprising:

[0053] The phosphate lithium aluminum stone powder is mixed with an inorganic acid and subjected to a first roasting treatment to obtain a clinker;

[0054] Mixing the clinker with water, performing a first leaching treatment, and obtaining a first leaching liquid and a first leaching residue through a first solid-liquid separation;

[0055] The first leaching solution is mixed with iron salt to carry out a dephosphorization reaction, and a dephosphorization liquid and a dephosphorization slag are obtained through a second solid-liquid separation;

[0056] The phosphorus removal liquid is mixed with aluminum salt and sodium salt to react, and the adsorbed liquid and lithium adsorbent are obtained through a third solid-liquid separation;

[0057] The lithium adsorbent is subjected to a second roasting treatment, the product after the second roasting is mixed with water, subjected to a second leaching treatment, and subjected to a fourth solid-liquid separation to obtain a lithium-rich solution and lithium-desorption slag;

[0058] The lithium-rich solution is subjected to impurity removal treatment and lithium precipitation treatment in sequence to obtain lithium carbonate.

[0059] According to the embodiment of the present application, the 200-mesh screening rate of the ferrite powder is greater than 95%. Thus, the material can be evenly heated during roasting, which is convenient for the subsequent leaching process.

[0060] According to some embodiments of the present application, the phosphate lithium aluminum stone powder is prepared by the following method: phosphate lithium aluminum stone is crushed and sieved to obtain the phosphate lithium aluminum stone powder.

[0061] According to an embodiment of the present application, the inorganic acid includes one of sulfuric acid, hydrochloric acid, and nitric acid;

[0062] And / or, the mass ratio of the phosphate lithium aluminum stone powder to the inorganic acid is 1: (0.3-0.8); when the mass ratio of the phosphate lithium aluminum stone powder to the inorganic acid is within the above range, the amount of the inorganic acid is sufficient to react chemically with the lithium component in the phosphate lithium aluminum stone to convert it into a soluble lithium salt, which can ensure the effective dissolution of lithium and ensure the high yield of lithium in the subsequent leaching process. If the amount of inorganic acid added is too little, the lithium cannot be completely converted into a soluble lithium salt, which leads to a low yield of lithium in the subsequent leaching process; if the amount of inorganic acid added is too much, it will not significantly increase the conversion amount of the soluble lithium salt, and will also increase the cost.

[0063] For example, the mass ratio of the phosphate lithium aluminum stone powder to the inorganic acid can be 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8 or any value between 1:(0.3-0.8).

[0064] And / or, the temperature of the first calcination treatment is 500°C to 700°C; when the temperature of the first calcination treatment is within the above range, it can ensure that the lithium component in the phosphate lithium aluminum stone fully reacts with the inorganic acid to convert it into a soluble lithium salt, and can also avoid sintering and improve process stability. If the temperature of the first calcination treatment is too low, it will lead to insufficient reaction and lithium cannot be completely converted into a soluble lithium salt, which will lead to a low lithium yield in the subsequent leaching process. If the temperature of the first calcination treatment is too high, sintering will occur, the material will agglomerate, and it will be difficult to leach it subsequently.

[0065] For example, the temperature of the first calcination process may be 500°C, 550°C, 600°C, 650°C, 700°C, or any value between 500°C and 700°C.

[0066] And / or, the time of the first calcination treatment is 1 hour to 3 hours. For example, the time of the first calcination treatment can be 1 hour, 2 hours, 3 hours or any value between 1 hour and 3 hours.

[0067] The reactions involved in the first calcination treatment are as follows:

[0068] LiAlPO4(OH,F)+H2SO4→Li2SO4+Al3(SO4)+AlPO4+H2O(2HF)

[0069] LiAlPO4(OH,F)+HCl→LiCl+AlCl3+AlPO4+H2O(2HF)

[0070] LiAlPO4(OH,F)+HNO3→LiNO3+Al(NO3)3+AlPO4+H2O(2HF)

[0071] According to an embodiment of the present application, when the first leaching treatment is carried out, the solid-liquid ratio of clinker to water is 1:(5-10) g / ml; for example, the solid-liquid ratio of clinker to water can be 1:5 g / ml, 1:6 g / ml, 1:7 g / ml, 1:8 g / ml, 1:9 g / ml, 1:10 g / ml or any value between 1:(5-10) g / ml.

[0072] And / or, the temperature of the first leaching treatment is 70° C. to 100° C.; at this temperature, lithium in the clinker can be leached quickly, thereby improving the leaching efficiency.

[0073] For example, the temperature of the first leaching treatment may be 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any value between 70°C and 100°C.

[0074] And / or, the time of the first leaching treatment is 0.5 h to 2 h. For example, the time of the first leaching treatment can be 0.5 h, 1 h, 1.5 h, 2 h, or any value between 0.5 h and 2 h.

[0075] According to an embodiment of the present application, the iron salt includes any one of iron sulfate, iron chloride, and iron nitrate, and the anion of the iron salt is the same as the anion of the inorganic acid;

[0076] And / or, the ratio of the amount of iron in the iron salt to the amount of phosphorus in the first leachate is 1.0 to 1.05; when the ratio is within the above range, the amount of iron salt is sufficient to react with the phosphorus in the first leachate to form an insoluble iron phosphate precipitate, which can effectively remove phosphorus, ensure that the phosphorus removal rate reaches a high level, avoid phosphorus interference with subsequent processes, and improve the overall process efficiency and product quality. If the above ratio is too small, it is equivalent to adding too little iron salt, which will cause incomplete phosphorus removal. If the above ratio is too large, it is equivalent to adding too much iron salt, which will increase production costs and cause waste.

[0077] For example, the ratio of the amount of iron in the iron salt to the amount of phosphorus in the first leachate may be 1.0, 1.01, 1.02, 1.03, 1.04, 1.05 or any value between 1.0 and 1.05.

[0078] And / or, when performing the phosphorus removal reaction, the method further includes adding sodium carbonate to the reaction system to adjust the system pH to between 1.5 and 1.8. This is conducive to the complete conversion of phosphorus in the first leachate into iron phosphate. If the pH is too low, there will be too much P and Fe to form iron phosphate precipitation. If the pH is too high, part of P will form aluminum phosphate precipitation with Al, and more aluminum salts will need to be added later, which increases the cost.

[0079] For example, the addition of sodium carbonate can adjust the pH of the system to 1.5, 1.6, 1.7, 1.8 or any value between 1.5 and 1.8.

[0080] According to an embodiment of the present application, the temperature of the phosphorus removal reaction is 90°C to 95°C; for example, the temperature of the phosphorus removal reaction can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C or any value between 90°C and 95°C.

[0081] And / or, the phosphorus removal reaction time is 1 h to 2 h. For example, the phosphorus removal reaction time can be 1 h, 1.5 h, 2 h or any value between 1 h and 2 h.

[0082] When the phosphorus removal reaction is carried out, the reactions involved are:

[0083] PO4 3- +Fe 3+ →FePO4

[0084] According to an embodiment of the present application, when the phosphorus removal liquid reacts with aluminum salt and sodium salt, the method further comprises: adding ammonia water to the reaction system to adjust the pH of the system to between 8.0 and 10; if the pH is too low, part of Al is precipitated in the form of Al(OH)3 and cannot be combined with LiY, and the purpose of the experiment cannot be achieved; if the pH is too high, part of Al is precipitated in the form of AlO2 - exists and re-enters the solution, unable to form LiY·2Al(OH)3·xH2O precipitate.

[0085] For example, adding aqueous ammonia to the reaction system can adjust the pH of the system to 8.0, 8.5, 9.0, 9.5, 10 or any value between 8.0 and 10.

[0086] and / or, the aluminum salt comprises any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion of the aluminum salt is the same as the anion of the inorganic acid;

[0087] and / or, the sodium salt comprises any one of sodium sulfate, sodium chloride and sodium nitrate, and the anion of the sodium salt is the same as the anion of the inorganic acid;

[0088] And / or, the amount of aluminum salt and sodium salt added is controlled so that after adding aluminum salt and sodium salt, the ratio of the amount of aluminum in the reaction system to the amount of lithium in the dephosphorization solution is 2-4, and the ratio of the amount of sodium in the sodium salt to the amount of aluminum in the reaction system is 3-5; when the ratio of the amount of Al:Li is too small or the ratio of the amount of Na:Al is too small, the Li in the dephosphorization solution cannot completely form LiY·2Al(OH)3·xH2O precipitation; when the ratio of the amount of Al:Li is too large or the ratio of the amount of Na:Al is too large, the lithium in the solution will not be significantly reduced after adsorption, and the purpose of adsorption has been achieved, and there is no need to add more aluminum salt and sodium salt.

[0089] For example, after adding aluminum salt and sodium salt, the ratio of the amount of aluminum in the reaction system to the amount of lithium in the dephosphorization liquid can be 2, 3, 4 or any value between 2 and 4, and the ratio of the amount of sodium in the sodium salt to the amount of aluminum in the reaction system can be 3, 4, 5 or any value between 3 and 5.

[0090] And / or, the temperature at which the dephosphorization solution reacts with the aluminum salt and the sodium salt is 80°C to 100°C; at this temperature, the collision of ions in the solution can be increased, and LiY·2Al(OH)3·xH2O precipitates can be easily formed.

[0091] For example, the temperature at which the phosphorus removal solution reacts with the aluminum salt and the sodium salt may be 80°C, 85°C, 90°C, 95°C, 100°C or any value between 80°C and 100°C.

[0092] And / or, the time for the phosphorus removal solution to react with the aluminum salt and the sodium salt is 2 hours to 4 hours. For example, the time for the phosphorus removal solution to react with the aluminum salt and the sodium salt can be 2 hours, 3 hours, 4 hours or any value between 2 hours and 4 hours.

[0093] Furthermore, when the phosphorus removal solution reacts with aluminum salt and sodium salt, the reactions involved are:

[0094] LiY+2AlY3+6NaOH→LiY·2Al(OH)3·xH2O↓+6NaY, where Y is (SO4) 1 / 2 ,

[0095] Cl or NO3.

[0096] According to the embodiment of the present application, the temperature of the second roasting treatment is 350°C to 600°C; at this temperature, it is conducive to the decomposition of LiY·2Al(OH)3·xH2O to generate soluble lithium salts, which is conducive to subsequent leaching. If the temperature of the second roasting treatment is too low, it will lead to incomplete decomposition, resulting in a reduced lithium yield. If the temperature of the second roasting treatment is too high, the problem of LiY volatilization will occur, resulting in a waste of lithium and increasing energy consumption.

[0097] For example, the temperature of the second calcination process may be 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, or any value between 350°C and 600°C.

[0098] And / or, the time of the second calcination treatment is 0.5 h to 2 h; for example, the time of the second calcination treatment can be 0.5 h, 1 h, 1.5 h, 2 h or any value between 0.5 h and 2 h.

[0099] Further, the reaction involved in the second calcination treatment is:

[0100] LiY·2Al(OH)3·xH2O→LiY+Al2O3+H2O, where Y is (SO4) 1 / 2 , Cl or NO3.

[0101] And / or, when the second leaching treatment is performed, the solid-liquid ratio of the second calcined product to water is 1:(3-5) g / ml; for example, the solid-liquid ratio of the second calcined product to water can be 1:3 g / ml, 1:4 g / ml, 1:5 g / ml or any value between 1:(3-5) g / ml.

[0102] And / or, the temperature of the second leaching treatment is 80°C to 100°C; at this temperature, the leaching process can be accelerated. For example, the temperature of the second leaching treatment can be 80°C, 85°C, 90°C, 95°C, 100°C or any value between 80°C and 100°C.

[0103] And / or, the time of the second leaching treatment is 0.5 h to 2 h. For example, the time of the second leaching treatment can be 0.5 h, 1 h, 1.5 h, 2 h, or any value between 0.5 h and 2 h.

[0104] According to an embodiment of the present application, the lithium-rich liquid is sequentially subjected to impurity removal treatment and lithium precipitation treatment, including: mixing the lithium-rich liquid with an alkaline solution, and obtaining a de-impurified liquid and calcium-magnesium slag through a fifth solid-liquid separation; and mixing the de-impurified liquid with sodium carbonate to obtain lithium carbonate.

[0105] According to the embodiments of the present application, the pH of the alkaline solution is 11 to 13; under this condition, calcium and magnesium impurities in the solution can be effectively removed. If the pH is too low, it will cause problems such as incomplete impurity removal and a high impurity content in the subsequently prepared lithium carbonate. If the pH is too high, the removal rate of calcium and magnesium impurities will not be significantly improved.

[0106] Further, the reaction involved in the impurity removal treatment is:

[0107] Ca 2+ +2OH - →Ca(OH)2

[0108] Mg 2+ +2OH - →Mg(OH)2

[0109] Furthermore, the reaction involved in the lithium precipitation treatment is:

[0110] 2Li + +CO3 2- →Li2CO3

[0111] And / or, the alkaline solution includes sodium hydroxide.

[0112] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0113] Example 1

[0114] The composition of pyroxenite includes: Li2O: 6.85%, Al2O3: 31.66%, P2O5: 47.96%. Example 1 provides a method for preparing lithium carbonate using pyroxenite, referring to Figure 1 ,include:

[0115] S1: grinding and sieving the phosphate lithium aluminum stone by ball milling to obtain the ball milled material, and the 200 mesh screening rate is 96.4%;

[0116] S2: the ball-milled material is mixed evenly with sulfuric acid at a mass ratio of 1:0.6, and roasted at 600°C for 2h to obtain clinker;

[0117] S3: adding water to the clinker for leaching, with a solid-liquid ratio of 1:8 g / ml, a leaching temperature of 80° C., and a leaching time of 1 h, and performing a first solid-liquid separation to obtain a leaching solution and a leaching residue;

[0118] S4: adding ferric sulfate to the leaching solution so that the ratio of the amount of Fe in the ferric sulfate to the amount of P in the leaching solution is 1.05, adding sodium carbonate to make the pH of the solution 1.5, reacting at a temperature of 95° C. for 2 hours, and performing a second solid-liquid separation to obtain a dephosphorization solution and a dephosphorization slag;

[0119] S5: adding aluminum sulfate and sodium sulfate to the dephosphorization solution, ensuring that the ratio of the amount of Al to the amount of Li in the solution is 3, and the ratio of the amount of Na to the amount of Al in the solution is 4, adding ammonia water to adjust the pH of the solution to 8.5, reacting at a temperature of 95° C. for 4 hours, and performing a third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent;

[0120] S6: calcining the lithium adsorbent at 350° C. for 2 h and then leaching with water, with a solid-liquid ratio of 1:3 g / ml, a leaching temperature of 90° C., and a leaching time of 2 h, and performing a fourth solid-liquid separation to obtain a lithium-enriched solution and lithium-desorption slag;

[0121] S7: adding sodium hydroxide to the lithium-rich solution to adjust the pH to 13, performing the fifth solid-liquid separation to obtain a decontaminated solution and calcium-magnesium slag, and adding sodium carbonate to the decontaminated solution to synthesize lithium carbonate.

[0122] Example 2

[0123] The composition of pyroxenite includes Li2O: 7.65%, Al2O3: 32.87%, and P2O5: 46.12%.

[0124] Embodiment 2 provides a method for preparing lithium carbonate using pyroxenite, comprising:

[0125] S1: grinding and sieving the phosphate lithium aluminum stone by ball milling to obtain the ball milled material, and the 200 mesh screening rate is 95.98%;

[0126] S2: the ball-milled material is evenly mixed with hydrochloric acid at a mixing mass ratio of 1:0.7, and roasted at 550°C for 2h to obtain clinker;

[0127] S3: adding water to the clinker for leaching, with a solid-liquid ratio of 1:10 g / ml, a leaching temperature of 90° C., and a leaching time of 1 h, and performing a first solid-liquid separation to obtain a leaching solution and a leaching residue;

[0128] S4: adding ferric chloride to the leachate to make the ratio of the amount of Fe in the ferric chloride to the amount of P in the leachate to be 1.03, adding sodium carbonate to make the pH of the solution 1.6, reacting at a temperature of 95°C for 1.5h, and performing a second solid-liquid separation to obtain a dephosphorization solution and a dephosphorization slag;

[0129] S5: adding aluminum chloride and sodium chloride to the dephosphorization solution, ensuring that the ratio of the amount of Al to the amount of Li in the solution is 4, and the ratio of the amount of Na to the amount of Al in the solution is 5, adding ammonia water to adjust the pH of the solution to 9, reacting at a temperature of 95° C. for 3 hours, and performing a third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent;

[0130] S6: calcining the lithium adsorbent at 550° C. for 1 h and then leaching with water, with a solid-liquid ratio of 1:4 g / ml, a leaching temperature of 90° C., and a leaching time of 0.5 h, and performing a fourth solid-liquid separation to obtain a lithium-enriched solution and lithium-desorption slag;

[0131] S7: adding sodium hydroxide to the lithium-rich solution to adjust the pH to 12, performing the fifth solid-liquid separation to obtain a decontaminated solution and calcium-magnesium slag, and adding sodium carbonate to the decontaminated solution to synthesize lithium carbonate.

[0132] Example 3

[0133] The composition of phosphate lithium aluminum stone includes: Li2O: 7.22%, Al2O3: 30.71%, P2O5: 48.55%.

[0134] Embodiment 3 provides a method for preparing lithium carbonate using pyroxenite, comprising:

[0135] S1: grinding and sieving the phosphate lithium aluminum stone by ball milling to obtain the ball milled material, and the 200 mesh screening rate is 96.7%;

[0136] S2: the ball-milled material is mixed evenly with nitric acid at a mass ratio of 1:0.6, and roasted at 600°C for 1h to obtain clinker;

[0137] S3: adding water to the clinker for leaching, with a solid-liquid ratio of 1:8 g / ml, a leaching temperature of 100° C., and a leaching time of 0.5 h, and performing a first solid-liquid separation to obtain a leaching solution and a leaching residue;

[0138] S4: adding ferric nitrate to the leachate to make the ratio of the amount of Fe in the ferric nitrate to the amount of P in the leachate to be 1.03, adding sodium carbonate to make the pH of the solution 1.8, reacting at a temperature of 95° C. for 1 hour, and performing a second solid-liquid separation to obtain a dephosphorization solution and a dephosphorization slag;

[0139] S5: adding aluminum nitrate and sodium nitrate to the dephosphorization solution, ensuring that the ratio of the amount of Al to the amount of Li in the solution is 2, and the ratio of the amount of Na to the amount of Al in the solution is 3, adding ammonia water to adjust the pH of the solution to 10, reacting at a temperature of 100° C. for 2 hours, and performing a third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent;

[0140] S6: the lithium adsorbent is calcined at 600° C. for 1 h and then leached with water, the solid-liquid ratio is 1:3 g / ml, the leaching temperature is 90° C., the leaching time is 2 h, and the fourth solid-liquid separation is performed to obtain a lithium-enriched solution and a lithium-desorption slag;

[0141] S7: adding sodium hydroxide to the lithium-rich solution to adjust the pH to 11, performing the fifth solid-liquid separation to obtain a decontaminated solution and calcium-magnesium slag, and adding sodium carbonate to the decontaminated solution to synthesize lithium carbonate.

[0142] Comparative Example 1

[0143] Comparative Example 1 provides a method for efficiently preparing lithium carbonate by using phosphate lithium aluminum stone to prepare lithium adsorbent. The difference from Example 1 is that the calcination temperature in step S2 of Comparative Example 1 is 400°C, and the other conditions are the same as Example 1.

[0144] Comparative Example 2

[0145] Comparative Example 2 provides a method for preparing lithium carbonate using lithium aluminum sulfate. The difference from Example 2 is that in step S5 of Comparative Example 2, the content of aluminum chloride and sodium chloride added is relatively small. After adding aluminum chloride and sodium chloride, the ratio of the amount of Al in the solution to the amount of Li can be ensured to be 1, and the ratio of the amount of Na in the solution to the amount of Al can be ensured to be 2. Other conditions are the same as those in Example 2.

[0146] Comparative Example 3

[0147] Comparative Example 3 provides a method for preparing lithium carbonate using lithium aluminum sulfate. The difference from Example 3 is that in step S6 of Comparative Example 3, the calcination temperature of the lithium adsorbent is 300°C, and the other conditions are the same as those of Example 3.

[0148] The effect data of preparing lithium carbonate in Examples 1-3 and Comparative Examples 1-3 are shown in Table 1.

[0149] Table 1 Comparison of the effects of preparing lithium carbonate in Examples 1-3 and Comparative Examples 1-3

[0150]

[0151]

[0152] Wherein, the lithium leaching rate of step S3 = (mass of lithium in the leaching solution of step S3 / (mass of lithium in the leaching solution of step S3 + mass of lithium in the leaching residue of step S3) * 100)%.

[0153] The lithium leaching rate of step S6 = (the mass of lithium in the lithium-enriched solution of step S6 / (the mass of lithium in the lithium-enriched solution of step S6 + the mass of lithium in the lithium decomposition slag of step S6) * 100)%.

[0154] Comprehensive lithium yield = lithium mass in product lithium carbonate / lithium mass in raw material pyrophyllite*100%.

[0155] From the comparison between Comparative Example 1 and Example 1, it can be seen that the lithium leaching rate and the comprehensive lithium recovery rate of step S3 of Comparative Example 1 are lower than those of step S3 of Example 1. This is mainly because the roasting temperature of step S2 in Comparative Example 1 is reduced, and part of the lithium in the lithium aluminum sulfate is not converted into soluble lithium, resulting in a decrease in the lithium leaching rate and the comprehensive lithium recovery rate.

[0156] From the comparison between Comparative Example 2 and Example 2, it can be seen that the lithium content in the liquid after adsorption in step S5 of Comparative Example 2 is significantly greater than the lithium content in the liquid after adsorption in step S5 of Example 2. This is mainly because the content of Al and Na added in step S5 of Comparative Example 2 is too small, resulting in incomplete conversion of lithium into LiY·2Al(OH)3·xH2O, which will cause part of the lithium to remain in the liquid after adsorption, resulting in an increase in the lithium content in the liquid after adsorption in Comparative Example 2.

[0157] From the comparison between Comparative Example 3 and Example 3, it can be seen that the lithium leaching rate and the comprehensive lithium yield of step S6 of Comparative Example 3 are significantly lower than those of step S6 of Example 3. This is mainly because the calcination temperature of the lithium adsorbent in step S6 of Comparative Example 3 is too low, which will lead to incomplete reaction and part of the lithium is not converted into soluble LiY, resulting in a decrease in the lithium leaching rate and the comprehensive lithium yield of step S6 in Comparative Example 3.

[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0159] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing lithium carbonate using pyroxenite, characterized in that: include: The phosphate lithium aluminum stone powder is mixed with an inorganic acid and subjected to a first roasting treatment to obtain a clinker; The clinker is mixed with water, and subjected to a first leaching treatment, and a first leaching liquid and a first leaching residue are obtained through a first solid-liquid separation; The first leaching solution is mixed with iron salt to perform a dephosphorization reaction, and a second solid-liquid separation is performed to obtain a dephosphorization liquid and a dephosphorization slag; The dephosphorization liquid is mixed with aluminum salt and sodium salt to react, and then subjected to a third solid-liquid separation to obtain an adsorbed liquid and a lithium adsorbent; The lithium adsorbent is subjected to a second roasting treatment, the product after the second roasting is mixed with water, subjected to a second leaching treatment, and subjected to a fourth solid-liquid separation to obtain a lithium-rich solution and lithium-desorption slag; The lithium-rich solution is sequentially subjected to impurity removal treatment and lithium precipitation treatment to obtain lithium carbonate.

2. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: The 200-mesh screening rate of the phosphate hematite powder is greater than 95%.

3. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: The inorganic acid includes one of sulfuric acid, hydrochloric acid and nitric acid; And / or, the mass ratio of the phosphate lithium aluminum stone powder to the inorganic acid is 1: (0.3-0.8); And / or, the temperature of the first calcination treatment is 500° C. to 700° C.; And / or, the first calcination treatment time is 1 hour to 3 hours.

4. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: When the first leaching treatment is performed, the solid-liquid ratio of the clinker to water is 1:(5-10) g / ml; and / or, the temperature of the first leaching treatment is 70° C. to 100° C.; And / or, the first leaching treatment time is 0.5h to 2h.

5. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: The iron salt includes any one of iron sulfate, iron chloride, and iron nitrate, and the anion of the iron salt is the same as the anion of the inorganic acid; and / or, the ratio of the amount of iron in the iron salt to the amount of phosphorus in the first leachate is 1.0 to 1.05; And / or, when performing the phosphorus removal reaction, the method further comprises adding sodium carbonate to the reaction system to adjust the pH of the system to between 1.5 and 1.

8.

6. The method for preparing lithium carbonate using pyroxenite according to claim 5, characterized in that: The temperature of the dephosphorization reaction is 90°C to 95°C; And / or, the phosphorus removal reaction time is 1 hour to 2 hours.

7. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: When the dephosphorization liquid reacts with the aluminum salt and the sodium salt, the method further comprises: adding ammonia water to the reaction system to adjust the pH of the system to between 8.0 and 10; And / or, the aluminum salt includes any one of aluminum sulfate, aluminum chloride, and aluminum nitrate, and the anion of the aluminum salt is the same as the anion of the inorganic acid; And / or, the sodium salt includes any one of sodium sulfate, sodium chloride, and sodium nitrate, and the anion of the sodium salt is the same as the anion of the inorganic acid; And / or, the amount of the aluminum salt and the sodium salt added is controlled so that after the aluminum salt and the sodium salt are added, the ratio of the amount of aluminum in the reaction system to the amount of lithium in the dephosphorization solution is 2 to 4, and the ratio of the amount of sodium in the sodium salt to the amount of aluminum in the reaction system is 3 to 5; And / or, the temperature at which the dephosphorization liquid reacts with the aluminum salt and the sodium salt is 80° C. to 100° C.; And / or, the phosphorus removal liquid reacts with the aluminum salt and the sodium salt for 2 hours to 4 hours.

8. The method for preparing lithium carbonate using pyroxenite according to claim 1, characterized in that: The temperature of the second calcination treatment is 350°C to 600°C; And / or, the second calcination treatment time is 0.5h to 2h; and / or, during the second leaching treatment, the solid-to-liquid ratio of the second calcined product to water is 1:(3-5) g / ml; and / or, the temperature of the second leaching treatment is 80° C. to 100° C.; And / or, the second leaching treatment time is 0.5h to 2h.

9. The method for preparing lithium carbonate using pyroxenite according to any one of claims 1 to 8, characterized in that: The lithium-rich solution is sequentially subjected to impurity removal treatment and lithium precipitation treatment, including: mixing the lithium-rich solution with an alkaline solution, and obtaining a de-impurified liquid and calcium-magnesium slag through a fifth solid-liquid separation; and mixing the de-impurified liquid with sodium carbonate to obtain lithium carbonate.

10. The method for preparing lithium carbonate using pyroxenite according to claim 9, characterized in that: The pH of the alkaline solution is 11 to 13; And / or, the alkaline solution comprises sodium hydroxide.